Unmet Needs and Classical Pitfalls in the Management of Adolescents With Behavioral Problems in Emergency - Guedj-Bourdiau, Marie-Jeanne; Guilé, Jean-Marc; Garny de la Rivière, Sébastien; Pace, Ugo; Cohen, David; Benarous, Xavier (Frontiers in Psychiatry, 2021)
While behavioral problems are the main reasons for adolescents to be referred to an emergency room for mental health problems, their clinical management remain usually heterogenous, poorly standardized, and associated with a low level of patient and family satisfaction. So far, most attention has been paid to the treatment of agitation, and few insights have been provided on the treatment plan of behavioral problems once the crisis is over and a psychiatric or medical condition ruled out. This perspective article represents an attempt to incorporate multiple theoretical approaches to provide a comprehensive and operational model for the management of adolescents with behavioral problems in an emergency department. Short hypothetical case vignettes illustrate the importance of considering several levels of analysis to understand the adolescent's problematic behavior which can be seen as a symptom of a medical/psychiatric condition (medical model), as a maladaptive strategy in a context of vulnerability (developmental model), and finally as a mode of communication in a context of ill-adapted relational patterns (systemic model). As behavioral problems in adolescence are a complex issue, frequently involving the intervention of professionals from various disciplines, being aware of such different levels of understanding could help to preclude any role confusion and to provide better targeted interventions.